More than words! A narrative review of the use of the projective technique of word association in the studies of food consumer behavior: Methodological and theoretical implications - Rivas Rojas, Edgard Alejandro (2022)
Word association (WA) is a projective and powerful technique that consists of the spontaneous generation of words from specific stimuli. This technique is used in sociology and psychology studies; however, in the Consumer and Food Science area has gained importance since it allows to explore beliefs, expectations, or attitudes in the context of food consumption behavior. The aim of this work is to present a current status on the use of this technique in the studies of food consumption behavior. A narrative review of the literature was carried out with articles published in four databases: ScienceDirect, Wiley Online Library, Emerald Insight, and Taylor & Francis. Seventy-four articles that show the use of the WA technique in different cultures were selected. WA technique has been applied in different countries, however, it has been primarily used in Latin America. WA has been applied mainly to decipher consumers' perceptions towards different aspects of food, although some works show that WA serves to understand beliefs, expectations, impressions, attitudes, and even to conceptualize different categories of food from the language of consumers. Some theoretical and methodological implications are discussed regarding the use and application of this projective technique.